Development of Android-based Kimi Kimo Adventure Game as Learning Media on Chemical Bonds - Kurniawan, Rivaldi Dwi; Hidayah, Rusly (International Journal of Active Learning, 2021)
This research aims to test the development of an android-based Kimi Kimo Adventure game which is feasible as a learning media for Chemical Bonding material at SMK Negeri 1 Driyorejo Gresik. The feasibility of the Kimi Kimo Adventure game is reviewed in terms of validity, practicality, and effectiveness. Validity in terms of content validity and construct validity obtained from the validation results of 3 experts, namely 2 chemistry lecturers at Universitas Negeri Surabaya and 1 chemistry teacher at SMK Negeri 1 Driyorejo Gresik. Practicality was obtained from the results of student observations and student response questionnaires. While the effectiveness is obtained from the students learning outcomes. The research method that was used is research and development carried out until a limited trial. The limited trial was carried out in 18 students from class X at SMK Negeri 1 Driyorejo Gresik. The data that has been obtained from the limited trial of the Kimi Kimo Adventure game has a percentage assessment of (1) Validity consisting of content validity which is very valid and construct validity which is very valid, (2) Practicality consisting from the observation result of student activities which is very practical and the results of the response questionnaire which is very practical, (3) Effectiveness consists the value of students’ learning outcomes and the classical completeness between the pretest and posttest has increased. It means the Kimi Kimo Adventure game as a learning media can increase the students’ learning outcomes which means the game that has been developed is very effective for use as learning media on chemical bonds. Based on the results of the research, it can be concluded that the Kimi Kimo Adventure game is appropriate for use as a learning medium.